Woman does not exist. A love letter - Bodea, Cristian (International journal on humanistic ideology, 2019)
In this paper I would like to develop the idea that there is a very clear distinction to be made between hysteria, on the one hand, and what psychoanalysis calls the feminine position, on the other hand. It is to the logic of the not whole that this feminine position corresponds, a logic that the hysteric subject contests at his/her turn. In this regard, hysteria is more close to a position attributed to men. What remains to be shown, in what follows, is what position the woman is in. If she does not exist, as the title of my paper suggests, then where is she?